MENYUSUTKAN RUGI – RUGI DAYA PADA PENYULANG MTL DAN PENYULANG BJM DENGAN MEREKONFIGURASI JARINGAN TEGANGAN MENENGAH - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
One way to optimize the flow of energy on a distribution channel is to reconfigure the network. This research aim to get optimal distribution system at PT.PLN Area Banjarmasin Penyulang BJM02, MTL04 and MTL10. The MTL10 repeater that will be recovered by reconfiguring the network to divide the load on the nearest repeater is the BJM02 and MTL04 feeders. This study uses 3 scenarios with regard to the state of the existing network to obtain a minimum power loss. In order to obtain a good conclusion then the analysis obtained that before the reconfiguration penyulang BJM02, MTL04 and MTL10 experienced energy losses 521,286 W. Resolving the problem then the network reconfiguration can be done on the BJM02 Repeater will divide the load of KST02 and the load of the earth in the circumference basirih earth in the feeder MTL04 to the MTL10 feeder. In configuring the network the thing that can be done is to open the KST02 circuit breaker at the KS.Tubun relay substance and close the disconneting switch (BJM02 Repeater) so that it connects with the MTL04 repeater. The MTL04 repeater will cut the muzzle throughput cable and connect the cable to the earth's basirih circular housing so that the load until KST02 is connected. The results obtained after reconfiguration can minimize power losses of 20,418 W.